Kepuasan Mahasiswa terhadap Kualitas Pelayanan di STMIK Masa Depan Tangerang - Muhamad Nashirul Haq; Kelly Maysari (Jurnal Disrupsi Bisnis, 2024)
The research was conducted to find out the level of satisfaction and what attributes are considered important by students to the quality of service at STMIK Masa Depan Tangerang.  Data collection was carried out by distributing a questionnaire containing 21 questions representing 5 dimensions of servqual. This questionnaire was filled out by 100 respondents who are students who are currently still actively studying at STMIK Masa Depan Tangerang using the Likert scale. The method chosen by the author is the servqual method, which is to find out the expectations, perceptions and gaps in quality that describe the level of customer satisfaction. Perceptions that are greater or equal to expectations describe student satisfaction while perceptions that are smaller than expectations describe student dissatisfaction, then the importance-performance method is used to find out what attributes are considered important by students and need to be prioritized by the campus.